Effects of Vibration-Reducible Cementitious Materials on the Acoustic and Structural Responses of Buildings Adjacent to Urban Railway Systems: A Numerical Approach - Siyu Wu; Sukhoon Pyo (International Journal of Concrete Structures and Materials)
Abstract Some studies have developed different kinds of vibration-reducible construction materials. However, no existing study has applied these materials in a building to prove their effectiveness at a structural level. Besides, much of the related research has focused only on measuring sound pressure or vibration levels within buildings adjacent to railway systems. Although some studies have provided methods to predict the vibration of a building structure, they cannot determine the train-induced sound pressure level simultaneously. Therefore, this study used the finite element model to simulate an existing building structure to prove the effectiveness of this method. Based on the combination of the acoustic and solid interaction modules in the finite element analysis method, the vibration and sound levels of buildings based on different kinds of vibration-reducible cementitious materials were estimated using different models. The results show that vibration-reducible cementitious materials can reduce vibration velocity and sound pressure levels by up to 7.1 dB and 5.2 dB with an increased floor height, respectively. In addition, reduced vibration can decrease structure-borne noise by up to 2.9 dB. A further parametric study shows that cementitious materials with a relatively high elastic modulus, a high damping loss factor, and low density can be effective for vibration and sound reduction.